Redesign the user interface (UI) and user experience (UX) for websites using the design thinking method - Muttaqin, Khairul; Fadillah, Nurul; Khairani, Rani (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2025)
The Samudra University Informatics Study Program website serves as a vital information hub for students and other users. The comfort and experience users gain when accessing a website are critical factors to consider when designing a user interface. Currently, the Informatics Study Program website is underutilized. Redesign efforts are necessary to optimize its functionality by developing an improved user interface. Data collection was conducted using evaluations and questionnaires to enhance the user-centered approach. The redesign was carried out using the design thinking method, with the interface designed using Figma tools. Design thinking is a solution-oriented design approach that aids in problem-solving and understanding user needs. Initial evaluations indicate that the average user satisfaction score was at a